Personal Data Protection Law Used in Mobile Phone Sim Card Registration in Indonesia - mahendri putri sholichah; Dewi Rumaisa (Notaire, 2018)
The growths of technology make the privacy of personal information become an important issue in most countries, including Indonesia. Utilization of personal data is common things in most of our activity within the cyberspace and in this case, even the advancement of technology cannot neglect the privacy of personal information. The abusing of the data record, especially the data that belongs to the personal data category, the information that exists within this data could go to the public when it is leaked. One of the cases related to the personal data abuse is registration of thirty mobile phone SIM cards using one person’s personal information without the consent of personal information owner. This paper explains about personal data cases related to the mobile phone SIM card registration, and from this case, some issues about the abusing of personal data will be taken as an example to give consideration for legislating personal data protection. Moreover, this paper also explores the purpose of personal data collection, sensitive data collection, limitation of data collection, storage of collected personal data, transfer of collected personal data, and deletion of collected personal data. This paper convinces the urgency drafting of personal data protection law for country likes Indonesia. Therefore it is hoped that this paper will become one of many considerations for the Indonesian government to include personal data protection law into their national legislation program and legislate the personal data protection law in recent times.